Mathematical Connections among Teachers in Mobile Cybereducation: How do they show themselves? - Rosa, Maurício [UNESP]; Da Silva Caldeira, João Paulo (My University, 2018)
This research aimed to investigate how teachers in Mobile Cybereducation establish mathematical connections between peers. In order to do so, it was provided an education course based on the conception of Cybereducation with mathematics teachers (ROSA, 2015), which considers Digital Technologies (DT) in the context of Mathematics Education as participants in the knowledge production movement. In addition, regarding Mobile Cybereducation, this knowledge production movement is purposely raised in an informal manner through the smartphone, in line with social networks. In this sense, smartphones were made available for mobile access to these online platforms, while the participants were dispersed geographically. Under this bias, we understand the being/participant connected to a mobile device and this links us to the corporeity of these participants in the Merleau-Ponty (2011) perspective, pointing out as a result that teachers establish mathematical connections between peers hyper-textually plugged in a ubiquitously way. This perspective suggests the act of education with DT that happens all the time and everywhere, so that the technological resource becomes part of us, expanding/potentializing the mathematical connections made in a shared way.
Conexões Matemáticas entre Professores em Cyberformação Mobile: Como se mostram?
Keywords: Differential calculus teaching; M-learning; Social networks; Teachers education